Impact of glycoengineering and antidrug antibodies on the anticancer activity of a plant‐made lectin‐Fc fusion protein. Issue 11 (19th August 2022) - Dent, Matthew; Mayer, Katarina L.; Verjan Garcia, Noel; Guo, Haixun; Kajiura, Hiroyuki; Fujiyama, Kazuhito; Matoba, Nobuyuki
Summary: Plants are an efficient production platform for manufacturing glycoengineered monoclonal antibodies and antibody‐like molecules. Avaren‐Fc (AvFc) is a lectin‐Fc fusion protein or lectibody produced in Nicotiana benthamiana, which selectively recognizes cancer‐associated high‐mannose glycans. In this study, we report the generation of a glycovariant of AvFc that is devoid of plant glycans, including the core α1, 3‐fucose and β1, 2‐xylose residues. The successful removal of these glycans was confirmed by glycan analysis using HPLC. This variant, AvFc ΔXF, has significantly higher affinity for Fc gamma receptors and induces higher levels of luciferase expression in an antibody‐dependent cell‐mediated cytotoxicity (ADCC) reporter assay against B16F10 murine melanoma cells without inducing apoptosis or inhibiting proliferation. In the B16F10 flank tumour mouse model, we found that systemic administration of AvFc ΔXF, but not an aglycosylated AvFc variant lacking affinity for Fc receptors, significantly delayed the growth of tumours, suggesting that Fc‐mediated effector functions were integral. AvFc ΔXF treatment also significantly reduced lung metastasis of B16F10 upon intravenous challenge whereas a sugar‐binding‐deficient mutant failed to show efficacy. Lastly, we determined the impact of antidrug antibodies (ADAs) on drug activity in vivo by pretreating animals with AvFc ΔXF before implanting tumours. Despite a significant ADA response induced by the pretreatment, we found that the activity of AvFc ΔXF was unaffected by the presence of these antibodies. These results demonstrate that glycoengineering is a powerful strategy to enhance AvFc's antitumor activity. Abstract : The plant‐produced lectibody Avaren‐Fc showed enhanced antitumor activity when the core fucose residue was removed from the Fc glycan. Anti‐drug antibodies appeared to augment antitumor efficacy, possibly through the lectibody's vaccinal effect.